Coverage of suicide in traditional media in colombia, before and during the pandemic (2018-2021) (2023)
The WHO made recommendations for the responsible publication of news about suicide, after the evidence of the effects of imitation of this behavior due to its inadequate transmission. The COVID-19 pandemic had a negative effect on the mental health of the human population, generating states of frank vulnerability. The main objective of this study was to analyze the characteristics of news about suicide published in traditional mass media in Colombia, before and during the COVID-19 pandemic (2018-2021), according to the aforementioned recommendations.